Comparison of Reactive Power Support in Distribution Networks Provided by Capacitor Banks and Distributed Generators - Rueda-Medina, A. C. [UNESP]; Lopez-Lezama, J. M. [UNESP]; Padilha-Feltrin, A. [UNESP] (IEEE, 2011)
This paper presents a comparison of reactive power support in distribution networks provided by switched Capacitor Banks (CBs) and Distributed Generators (DGs). Regarding switched CBs, a Tabu Search metaheuristic algorithm is developed to determine their optimal operation with the objective of reducing the power losses in the lines on the system, while meeting network constraints. on the other hand, the optimal operation of DGs is analyzed through an evolutionary Multi-Objective (MO) programming approach. The objectives of such approach are the minimization of power losses and operation cost of the DGs. The comparison of the reactive power support provided by switched CBs and DGs is carried out using a modified IEEE 34 bus distribution test system.
Keywords: Evolutionary multi-objective programming; distributed generation; reactive power support; power losses; Tabu Search